Impactos ambientais em espeleotemas causados pela visitação pública com carbureteiras na caverna santana (Parque Estadual Turístico do Alto Ribeira, Iporanga-SP) - Lobo, Heros Augusto Santos; Boggiani, Paulo César; Sayeg, Isaac Jamil; Perinotto, José Alexandre de Jesus [UNESP] (My University, 2015)
Calcium carbide is a chemical compound artificially produced by the combination of coal and limestone. It has been widely used as fuel for simple devices called carbide lamps which are used as a source of light in the exploration and tourist visitation of caves. Inside the lamp, the carbide reacts when mixed with water and releases acetylene, which is a flammable gas that fuel the fire-based illumination. Santana Cave (State Tourist Park of Alto Ribeira-SP) has been regularly visited both for tourism and research since the 70’s, and the visible darkening on its speleothems has been attributed to the use of carbide lamps, which are prohibited inside the said cave since 2003. To check this hypothesis, samples from speleothems were collected for mineral investigation with the aid of optical and electronic microscope and complemented by chemical analyses. The signs of physical changes and carbon residues that were noticed under the microscope, together with the presence of approximately 0.45[%] of residual carbon identified by chemical analysis, prove the negative impact of the usage of carbide lamps inside caves. The conclusion reinforces the need to restrain the use of carbide lamps inside caves, with tourist purposes, either because of the risks to the cave visitors.
Environmental impacts on speleothems caused by public visitation with carbide lamps in Santana Cave (State Tourist Park of Alto Ribeira, Iporanga-SP)